EXPLORING HEIMAT: CULTURAL BELONGING, IDENTITY, AND POWER DYNAMICS IN MADHURI VIJAY'S THE FAR FIELD (Al-Aasar, 2025)
This paper examines the concept of Heimat — the German concept of home, cultural belonging, and identity — in Madhuri Vijay’s The Far Field. The concept of Heimat has evolved to describe postmodern and transnational identities. The study aims to explore the transcultural influences that interfere in the characters’ perception and experience of Heimat, to present the socio-political context of the novel that shapes the negotiation and the construction of the individual identities, and to analyze the characters’ self-perceptions that are caused by power dynamics. This research uses a qualitative research methodology with the interpretivist approach. This article highlights how locating the concept of Heimat in the Indian literary context contributes to the larger discussion on the idea of belonging and identity in an age of globalization. It demonstrates how Heimat is a fluid and evolving entity, one that is constantly reconstituted and remapped through processes of transcultural exchange by socio-political shifts and transformations. Further research could help illustrate different cultural perceptions of home and belonging across various literary texts through the lens of Heimat.